Diversity of multi-drug resistant Acinetobacter baumannii population in a major hospital in Kuwait - Vali, Leila; Dashti, Khadija; Opazo-Capurro, Andrés F.; Dashti, Ali A.; Al Obaid, Khaled; Evans, Benjamin A. (Frontiers in Microbiology, 2015)
Acinetobacter baumannii is one of the most important opportunistic pathogens that causes serious health care associated complications in critically ill patients. In the current study we report on the diversity of the clinical multi-drug resistant A. baumannii in Kuwait by molecular characterization. One hundred A. baumannii were isolated from one of the largest governmental hospitals in Kuwait. Following the identification of the isolates by molecular methods, the amplified blaOXA-51-like gene product of one isolate (KO-12) recovered from blood showed the insertion of the ISAba19 at position 379 in blaOXA-78. Of the 33 multi-drug resistant isolates, 28 (85%) contained blaOXA-23, 2 (6%) blaOXA-24 and 6 (18%) blaPER-1 gene. We did not detect blaOXA-58, blaVIM, blaIMP, blaGES, blaVEB and blaNDM genes in any of the tested isolates. In 3 blaPER-1 positive isolates the genetic environment of blaPER-1 consisted of two copies of ISPa12 (tnpiA1) surrounding the blaPER-1 gene on a highly stable plasmid of ca. 140-kb. MLST analysis of the 33 A. baumannii isolates identified 20 different STs, of which 6 (ST-607, ST-608, ST-609, ST-610, ST-611 and ST-612) were novel. Emerging STs such as ST15 (identified for the first time in the Middle East), ST78 and ST25 were also detected. The predominant clonal complex was CC2. PFGE and MLST defined the MDR isolates as multi-clonal with diverse lineages. Our results lead us to believe that A. baumannii is diverse in clonal origins and / or is undergoing clonal expansion continuously while multiple lineages of MDR A. baumannii circulate in hospital wards simultaneously.